Brazil and the United States during World War II and Its Aftermath Negotiating Alliance and Balancing Giants - McCann, Frank D. (Springer International Publishing : Imprint: Palgrave Macmillan, 2018)
XVIII, 318 p. 18 illus., 1 illus. in color.